The Cowgirl and the Country M.D. - Mann, Catherine (Mann, Catherine. Top Dog Dude Ranch., 2022)
After putting her dreams on hold to care for her aging parents, Eliza Hubbard is finally ready to focus on her career. A coveted job as stable manager at a legendary ranch is just what the doctor ordered. But pediatrician Nolan Barnett isn't like any M.D. Eliza ever met. Between sleigh rides, rodeo demos and animal puppet shows, the sexy widower and his two orphaned grandkids are melting her resolve. Even Nolan isn't immune to the magic of moonlight...or a renewed desire to put down roots...